The Impact of The Sustainability Report on The Performance of Maqashid Sharia Islamic Commercial Banks in Indonesia - Arini, Arini; Maharani, Satia Nur; Juliardi, Dodik (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
This study examines the effect of sustainability reports on the performance of maqashid sharia in Islamic banks. The sample of this research is Islamic commercial banks in Indonesia for the period 2014-2018. The sustainability report is measured by the standard score of the GRI 4 sustainability report and the performance of Islamic banks is measured using maqashid sharia with 3 perspectives, namely education, justice and welfare. The method used is panel data regression with 3 research models. The results of the analysis of model 1 show that the sustainability report has a significant negative effect on the performance of maqashid sharia from an education perspective. In model 2, the results show that the sustainability report does not have a significant effect on the performance of maqashid syariah justice perspective. Model 3 shows the results that the sustainability report does not have a significant effect on the performance of maqashid syariah from the welfare perspective.